THE RISE OF CONTINENTS - AN ESSAY ON THE GEOLOGIC CONSEQUENCES OF PHOTOSYNTHESIS - Rosing M.T.; Bird D.K.; Sleep N.H.; Glassley W.; Albarede F. (My University, 2006)
Earth accreted 4567 Myr ago from largely homogeneous material. From this initial capital of matter, differentiation formed the chemical and physical compartments of core, mantle, continents, ocean and atmosphere, that characterize Earth today. Differentiation was, and still is, driven by energy from various sources including radioactive heat and relic heat from accretion. With evolution of photosynthesis, living organisms acquired the ability to harvest Solar energy and channel it into geochemical cycles. On our present Earth, the primary production from life contributes 3 times more energy to these cycles than Earth's internal heat engine. We hypothesize that the emergence of this energy resource modified Earth's geochemical cycles and ultimately stimulated the production of granite during the earliest Archaean, which led to the first stabilization of continents on Earth. Such biological forcing may explain the unique presence of granite on Earth, and why stable continents did not form during the first half billion years of Earth's history. © 2006 Elsevier B.V. All rights reserved.
Keywords: ARCHAEAN; CHLOROPHYLL; CONTINENTS; GRANITE; PHOTOSYNTHESIS; Precambrian::Archean; Докембрий::Архей